The stability of initial tacrolimus concentration following allogeneic hematopoietic stem cell transplantation reduces the risk of acute GVHD. Issue 10 (12th August 2020) - Okabe, Motohito; Morishita, Takanobu; Ichiki, Tomoe; Kawaguchi, Yuka; Lee, Yoonha; Ohbiki, Marie; Goto, Miyo; Osaki, Masahide; Araie, Hiroaki; Goto, Tatsunori; Ozawa, Yukiyasu; Miyamura, Koichi
Abstract: Background: Early tacrolimus (TAC) concentrations correlate with the risk of acute graft‐versus‐host disease (aGVHD); however, whether the variability of early TAC concentrations after allo‐HSCT governs the occurrence of aGVHD remains unknown. Here, we evaluate the correlation between the intrapatient variability (IPV) of initial TAC concentrations and the development of aGVHD. Methods: We retrospectively assessed 202 patients who underwent allo‐HSCT and received standard GVHD prophylaxis by continuous intravenous (iv) infusion of TAC and iv methotrexate. IPV was calculated by using the % coefficient of variation in the initial 4 weeks. Results: With median follow‐up duration of 20.7 months, 24 patients were diagnosed with grades II‐IV aGVHD. Overall survival (OS) and relapse at 12 months after allo‐HSCT were 70.6% (95% confidence interval [CI], 63.7%‐76.4%) and 18.9% (95% CI, 13.0%‐24.4%), respectively. When IPV was categorized into two groups (high: ≥9.5%; low: <9.5%), the cumulative incidence of grades II‐IV aGVHD was greater in the IPV‐high group at week 3 (odds ratio: 4.15; 95% CI, 1.37%‐12.6%, P  = .01). No significant differences were observed in OS and relapse between the two groups. Conclusion: We concluded that adjusting early TAC concentration stable may reduce aGVHD after allo‐HSCT without affecting the relapse rate.